Tualang honey formulation as potential osteoarthritis treatment: in-vitro cytotoxicity outcome - Zulkifly, Ahmad Hafiz; Abd. Rahim, Nour El Huda; Mohd Jan, Nurul Hafiza; Mohamad Amri, Nur Fathonah; Ibrahim, Mohd Zulfadzli; Hassan, Habibah; Rajab, Nor Fadilah (Malaysian Orthopaedic Association, 2024)
INTRODUCTION: Osteoarthritis (OA) is a degenerative joint disease affecting millions worldwide. In the orthopaedic field, viscosupplementation is widely used as an option treatment for pain relief among osteoarthritis patients as it acts as a lubricant in the joints. Tualang Honey Formulation (THF), a patented (patent no. MY179303-A) viscosupplement, is being investigated as a potential treatment for OA. This study aimed to evaluate the biocompatibility of THF by assessing cell viability upon exposure.